A DFT + U study on structural, electronic, vibrational and thermodynamic properties of TiO2 polymorphs and hydrogen titanate: tuning the Hubbard 'U-term'. (8th December 2017) - German, Estefania; Faccio, Ricardo; Mombrú, Alvaro W
Abstract: Structural, electronic, vibrational and thermodynamic properties have been tested when Hubbard parameter U is implemented in density functional theory calculations for TiO2 polymorphs: anatase, rutile, TiO2 –B and for hydrogen titanate (H2 Ti3 O7 ) bulk. Optimum U parameter values were found for each system, balancing geometric changes and electronic properties, namely, U = 4 eV for anatase and TiO2 –B, U = 5 eV for rutile and hydrogen titanate. Although the addition of this parameter improves the prediction of electronic properties, with no significant structural changes, we found that it would not be adequate for predicting vibrational properties.